Elastic scattering of electrons by Sr atom: a study of critical minima and spin polarization. (10th June 2019) - Kumar, Ashok; Abdullah, M N A; Haque, A K F; Singh, Indu; Uddin, M Alfaz
Abstract: Within the framework of the complex optical potential, the critical minima (CM) in the differential cross sections and the spin polarization in the elastic scattering of electrons by the Sr atom are studied in the energy range E i = 1–1000 eV using the Dirac and Schrödinger partial wave methods. The two methods are, respectively, termed as the optical potential method of Dirac (OPMD) and optical potential method of Schrödinger (OPMS). The differential cross sections (DCSs), total cross sections (TCSs), momentum transfer cross sections (MTCSs), integral elastic cross sections (IECSs), viscosity cross sections (VCSs) and inelastic cross sections (INCSs) for e –Sr scattering are also calculated for the same energy range. In OPMD, the complex optical potential is composed of the static, exchange, polarization and absorption potentials. The OPMS potential, on the other hand, comprises the static, local exchange, polarization, spin-orbit, and absorption components. The number of CM points has been found to be respectively 7 and 5 with OPMD and OPMS methods in the DCSs of e –Sr scattering. The number of maximum spin polarization points observed is 13 and 10 for the OPMD and OPMS respectively. The energy dependence of TCS, MTCS, IECS, VCS, and INCS, studied in this work, show a non-monotonous pattern for energies beyond about 50 eV. So far as we are concerned, this is the first work for the study of CM in the DCSs of the e –Sr scattering as there are neither experimental nor theoretical studies published in the literature for the same.